Acute Endovascular Treatment of Patients With Ischemic Stroke From Intracranial Large Vessel Occlusion and Extracranial Carotid Dissection - Compagne, Kars C. J.; Goldhoorn, R. B.; Uyttenboogaart, Maarten; van Oostenbrugge, Robert J.; van Zwam, Wim H.; van Doormaal, Pieter J.; Dippel, Diederik W. J.; van der Lugt, Aad; Emmer, Bart J.; van Es, Adriaan C. G. M.; , the MR CLEAN investigators (Frontiers in Neurology, 2019)
Introduction: Carotid artery dissection (CAD) and atherosclerotic carotid artery occlusion (ACAO) are major causes of a tandem occlusion in patients with intracranial large vessel occlusion (LVO). Presence of tandem occlusions may hamper intracranial access and potentially increases the risk of procedural complications of endovascular treatment (EVT). Our aim was to assess neurological, functional and technical outcome and complications of EVT for intracranial LVO in patients with CAD in comparison to patients with ACAO and to patients without CAD or ACAO. Methods: We analyzed data of the MR CLEAN trial intervention arm and MR CLEAN Registry, acquired in 16 Dutch EVT-centers. Primary outcome was the change in stroke severity by comparing the National Institute of Health Stroke Scale (NIHSS) score at 24-48 hours after treatment versus baseline. Secondary outcomes included reperfusion rate and symptomatic intracranial hemorrhage (sICH). We compared outcomes and complications between patients with CAD versus patients with ACAO and patients without CAD or ACAO. Results: In total, we identified 74 (4.7%) patients with CAD, 92 (5.9%) patients with ACAO and 1398 (89.4%) patients without CAD or ACAO. Neurological improvement at short-term after EVT in patients with CAD was significantly better compared to ACAO (resp. mean -5 versus mean -1 NIHSS point; p=0.03) and did not differ compared to patients without CAD or ACAO (-4 NIHSS points; p=0.62). Rates of successful reperfusion in patients with CAD (47%) was comparable to patients with ACAO (47%; p=1.00), but was less often achieved compared to patients without CAD or ACAO (58%; p=0.08). Occurrence of sICH did not differ significantly between CAD patients (5%) and ACAO (11%; p=0.33) or without CAD/ACAO (6%; p=1.00). Conclusion: EVT in patients with intracranial LVO due to CAD results in neurological improvement comparable to patients without tandem occlusions. Therefore, carotid artery dissection by itself should not be a contraindication for endovascular treatment in stroke patients with intracranial large vessel occlusion. Although more challenging endovascular procedures are to be suspected in both patients with CAD or ACAO, accurate distinction between CAD and ACAO might influence clinical decision making as better clinical outcome can be expected in patients with CAD.